Graph-Theory-Based Derivation, Modeling, and Control of Power Converter Systems - Li, Yuzhuo; Kuprat, Johannes; Li, Yunwei; Liserre, Marco (IEEE journal of emerging and selected topics in power electronics, 2022)
Graph-theoretical approaches have been widely applied in many disciplines, however, their implementation in power electronics converters and systems is still in the exploring stage. In this overview, we summarize the milestones and general applications of this powerful mathematical tool and illustrate its unique benefits in some emerging/challenging power electronics research topics, for example, systematic converter derivation and modeling, advanced control, and so on. Given the multidiscipline nature of power electronics, graph theory can serve as a bridge for experts in different disciplines with a universal framework for complex problems. With solid mathematical foundations, it can stimulate research of topological aspects in both converter and systematic levels, fits well for nowadays power electronics converter. It is hoped that this article can serve as a timely and handy summary for engineers/students who want to enter the field and promote the innovation of power-electronics-enabled applications.